Enhancing Structural Resilience: Exploring the Novel Sleeve Method for Steel T-Stub Connections - Atar, Muhammed; Çete, Berat (My University, 2024)
A new sleeve device has been introduced with the aim of enhancing the performance of steel structures under extreme loading conditions. Previous research has primarily focused on numerical simulations of this sleeve's application, emphasizing the need for further investigation to validate its effectiveness. This research paper presents a numerical analysis that explores how the sleeve device influences the deformation capacity and strength of a bolt up to the point of failure. The study involved the use of a T-stub connection with multiple sleeves, each featuring different geometric parameters. To assess the impact on strength and deformation capacity, a comparison was drawn between these findings and the behavior of a T-stub bolted connection without using the sleeve. In addition, Finite Element (FE) models were employed for additional parametric studies. The test outcomes demonstrated a substantial increase in the deformability of the bolted connection when utilizing the sleeve device, all the while preserving the strength and initial stiffness of the bolts. This proposed sleeve method in the study significantly enhances the connection's capacity by delaying bolt failure.
Keywords: Steel structures; T-stub connection; Steel sleeve; Bolted connection; Ductility.